Demographic variables associated with Covid-19 mortality - José Manuel Madrazo Cabo; Nuvia Adriana Monter Valera; Edith Jocelyn Hernández Sánchez; Mariola Ruiz Sánchez; Gabriela Sánchez Machorro; Crishelen Kurezyn-Díaz (SAGE Publishing, 2020)
Objectives: Covid-19 is a betacoronavirus that was initially transmitted to humans from an animal host. It enters the cell by binding its protein S with angiotensin-converted enzyme receptors. It is transmitted through direct contact and respiratory drops. The most affected population so far are older adults and people with chronic conditions. The objective of this research is to analyze the possible association between the structure of the population pyramid, the Gross Domestic Product, the type of isolation and screening used to detect Covid-19 in the countries with the highest and lowest mortality from this disease. Design and Methods: Some variables take part in the Covid-19 mortality worldwide, such as the population structure, expressed in the population pyramid by country, the type of isolation adopted in each nation, the Gross Domestic Product (GDP) as well as the type of screening that is implemented in the different countries analyzed. Results: After analyzing the mean difference in the countries with a regressive and progressive population pyramid, an association was identified between the regressive population pyramid structure and the higher mortality rate (p<0.001). Conclusions: The countries with a progressive population pyramid are the most benefited by making their population more screened since the mortality rate decreases significantly compared to the countries with less attribution (p<0.036).